Exploring the Impact of Generative AI Tools on English Writing Skills among English Education Exploring the Impact of Generative AI Tools on English Writing Skills among English Education Students : A Case Study of Students at Universitas Muhammadiyah Semarang (UNIMUS) - Silvia Nanda Putri Erito; Testiana Deni Wijayatiningsih (English Language Education Department, Universitas Majalengka, 2025)
The integration of generative artificial intelligence (AI) tools, such as ChatGPT, Grammarly, and QuillBot, has transformed the way students develop and refine their writing skills in higher education. This study aims to explore how English Education students at the University of Muhammadiyah Semarang (UNIMUS) perceive and utilize these tools to enhance their English writing competence. Using a qualitative research design, data were collected through an open-ended questionnaire distributed to 23 students who had experience using AI-based writing assistants. The responses were analyzed thematically following Braun and Clarke’s (2021) framework to identify patterns in students’ perceptions, experiences, and challenges. The findings indicate that while students view AI tools as helpful companions for improving grammar, vocabulary, and text organization, they also acknowledge risks such as overreliance and reduced creativity. These insights emphasize the importance of promoting AI literacy and responsible tool usage among future English teachers. Overall, the study contributes to the ongoing discussion on digital transformation in English language education and offers practical implications for integrating AI-assisted writing tools in higher education settings. Keywords: generative AI, English writing skills, English Education students, ChatGPT, qualitative research